THE EFFECT OF SUBTITLED ANIMATED CARTOON VIDEOS ON STUDENTS’ READING COMPREHENSION (A Quasi Experimental Study at The Sixth Grade Students of SDIT Al- Hasanah Kota Bengkulu) - Gustian Pelani (Journal of Applied Linguistics and Literature)
Thisstudyaims toinvestigatewhetheror nottheuseofsubtitledanimated cartoonvideosaffectstudents’ reading comprehension and to findoutinwhat performanceof reading comprehension aspectstheexperimentaland controlclassdiffer. ThepopulationincludedallthesixthgradestudentsofSDITAlHasanahKotaBengkulu in  academic  year  2015/2016,  which  consisted  of  77  students.  The  sampleswere  52 studentsthatwere taken fromtwo classes.Theexperimentalclass receiveda treatmentby usinganimatedcartoonvideoswithbimodalsubtitles, while thecontrolclasswas taught byusinganimatedcartoonvideoswithoutsubtitles.A pre-testwasgiven tobothclasses beforetreatment.Thedata wereanalyzedbyusingSPSS16for t-testformula.Theresults show that, firstly, therewasa statistically significantdifferencebetween thegroups in readingcomprehension scores.Therefore, itwasconcluded thattheuse ofsubtitled animated cartoon videoscould improvestudents’ reading comprehension. Secondly, for reading  comprehension  aspects,  the  experimental  class  and  the  control  class  were different inthe literalperformanceaspect.However,intheinferenceperformance,it showed  no  significant  difference.  Based  on  the  results,  it  wasrecommended  to  use subtitled animatedcartoonvideosastheteaching aidinteachingreadingcomprehension